Islamic Religious Education and Digital Citizenship: Preparing Muslim Youth for Ethical Participation in the Global Digital Society - Ahmad Nabriz; Ahmad Faizal Syahrul Azmi; Abubaker Kashada; Rahmat Ullah; Ajoy Chandra (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to examine the role of Islamic Religious Education in preparing Muslim youth for ethical participation in the global digital society and to develop a conceptual framework that integrates Islamic educational values with contemporary digital citizenship competencies. The study employed a qualitative library research approach through a systematic review and thematic analysis of scholarly literature on Islamic education, digital citizenship, digital ethics, character education, media literacy, and youth development published between 2021 and 2026. Data were collected from peer-reviewed journal articles, academic books, policy reports, and international educational guidelines and analyzed using thematic content analysis. The findings reveal that Islamic Religious Education provides a strong ethical and philosophical foundation for digital citizenship through the principles of ta‘lim (knowledge acquisition), tarbiyah (holistic development), ta’dib (ethical formation), akhlaq (moral character), amanah (trustworthiness), and tabayyun (information verification). The study identifies several essential competencies for Muslim youth, including digital literacy, critical media literacy, ethical online communication, responsible digital participation, intercultural understanding, and civic engagement. The novelty of this study lies in the development of the Islamic Digital Citizenship Framework (IDCF), which integrates Islamic Religious Education, digital citizenship theory, digital ethics, character education, and global citizenship into a comprehensive model for preparing Muslim youth to navigate digital environments responsibly. The study concludes that digital citizenship should be understood as a holistic educational process that promotes ethical responsibility, social engagement, and human flourishing in an increasingly interconnected digital society.